Strategi Pengembangan Bisnis Usaha Makanan Dalam Menetapkan Harga Produk Pada Usaha Ayam Geprek D&A - Ni Luh Dinda Novyanti; Setiawan Mandala Putra; Harnida Wahyuni Adda (Jurnal Riset dan Inovasi Manajemen, 2023)
This activity aims to find out how the food business development strategy is in setting product prices in the D&A geprek chicken business. The implementation method used is how to determine the time and duration of the activity and the place where the activity will be carried out. Determine the location where to market the product and provide the necessary tools and materials. Carry out the process of production, packaging, and how to market the product. Set the price and product quality in order to compete with other competitors in the city of hammer. The results of this activity show that D&A's Geprek Chicken can compete with other Geprek sellers in Palu City, due to the lower price setting strategy compared to other sellers. And during this activity, D&A's geprek chicken was able to sell geprek chicken according to the turnover target, even more than the turnover target.